2015
DOI: 10.1016/j.buildenv.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to particulate matter and ozone of outdoor origin in Singapore

Abstract: a b s t r a c tEstimates of population exposure to ambient air pollution traditionally rely on concentrations measured at central-site monitors as a surrogate for concentrations to which people are exposed. In this study of Singapore, we estimate population-averaged exposure concentrations for PM 2.5 , PM 10 , and O 3 by applying a model and data that account for age and gender demographics, intraurban regional variability, and microenvironmental effects with age-and gender-stratified time-activity budgets. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Participants spent the large majority of their time in three microenvironment categories: 61% at home, 26% at work, 7% in transit, and spent only 1% outdoors. These time-activity budget values agree reasonably well with a recent modeling study of exposures to particulate matter and ozone in Singapore that reported 70%, 28%, 3.2%, and 4.5%, at home, at work, transit, and outdoors respectively [29]. Differences in daily integrated CO2 exposures appear not to be driven by differences in behavior across groups as no statistically significant differences in comparisons of timemicroenvironment-activity budgets are observed (see Table S3 in the SI).…”
Section: Estimates Of Time Integrated Co2 Exposures and Time Activitysupporting
confidence: 79%
“…Participants spent the large majority of their time in three microenvironment categories: 61% at home, 26% at work, 7% in transit, and spent only 1% outdoors. These time-activity budget values agree reasonably well with a recent modeling study of exposures to particulate matter and ozone in Singapore that reported 70%, 28%, 3.2%, and 4.5%, at home, at work, transit, and outdoors respectively [29]. Differences in daily integrated CO2 exposures appear not to be driven by differences in behavior across groups as no statistically significant differences in comparisons of timemicroenvironment-activity budgets are observed (see Table S3 in the SI).…”
Section: Estimates Of Time Integrated Co2 Exposures and Time Activitysupporting
confidence: 79%
“…Ambient air pollutants containing copper, iron, potassium, nickel, silicon, vanadium, and zinc, with a particle size of between 2.5 and 10 microns, and ozone gas easily find their way into these houses through the natural ventilation, in turn contributing to household air pollution 12 . In particular, houses that are close to traffic-heavy roads, which are populated with vehicles using diesel as fuel, tend to have a higher load of household air pollutants.…”
Section: Sources Of Household Air Pollutionmentioning
confidence: 99%
“…This was particularly preferred for extended population studies, as well as for economic reasons. However, as these measurements do not take into account the existence of a personal cloud of each individual, they usually result in poor correlations of personal exposure with ambient concentrations [14][15][16][17][18]. These limitations were overtaken by the development of light-weight passive ozone samplers [19] for the assessment of personal exposure to O 3 , which have been used to a large extent since then [3,5,17,18,[20][21][22][23][24][25], and still comprise a reliable [26] and cost-effective method.…”
Section: Introductionmentioning
confidence: 99%